Bovine leptospirosis as a cause of reproductive failure (Revista Sistemas de Producción Agroecológicos, 2014)
Leptospirosis is a zoonotic infectious disease with global distribution, this disease is caudate spirochetal genus Leptospira species: L. interrogans and L. biflexa (as phenotypic classification) or L. interrogans, L. biflexa and L. kirschneri (based genotypic classification). The virulence factors associated with pathogenic Leptospira are endotoxins, hemolysins sphingomyelinase, phospholipase and surface adhesion proteins. In cattle found Leptospira borgpetersenii Serovar hardjo type hardjo bovis as an adapted serovar, and Leptospira interrogans serovar hardjo type hardjo prajitmo the species interrogans, L. icterohaemorrhagiae, L. canicola and L. grippotyphosa as a non-adapted serovars. Globally Leptospira hardjo is not the only pathogen associated with reproductive failure and it is not the only serovar of Leptospira found in cattle. The immunity presented against Leptospirosis is of humoral type. The microorganism has an incubation period of 4-10 days, spreads on liver, kidneys, lungs, reproductive tract (placenta) and cerebrospinal fluid, causing damage to the endothelium of blood vessels, organs localized ischemia, renal tubular necrosis, hepatocellular and lung damage, meningitis, myositis and placentitis. Toxic substances cause lysis of erythrocytes and cross the placenta causing fetal death by anoxia ending in 1-2 days after abortion.
Keywords: abortion; leptospirosis; L. hardjo; L. prajitmo; placentitis